European Breast Cancer Conference manifesto on breast centres/units. (February 2017) - Cardoso, Fatima; Cataliotti, Luigi; Costa, Alberto; Knox, Susan; Marotti, Lorenza; Rutgers, Emiel; Beishon, Marc
Abstract: Manifesto — CALL TO ACTION : The 2016 deadline for all patients in European Union countries to access specialist, multidisciplinary breast cancer units or centres, will be missed by most countries, despite numerous resolutions and declarations issued since the year 2000 that have called for universal specialist services. This means that many women, and some men, do not receive optimal breast cancer care in Europe. We call on policymakers and politicians to ensure, as soon as possible, that all women and men with breast cancer in Europe are treated in a specialist breast unit . To do this, we ask that policymakers and politicians, together with healthcare professionals and patient advocates: - Promote, in public and professional settings, the evidence that breast units staffed with specialist multidisciplinary teams deliver superior care and quality of life to women and men with breast cancer. - Acknowledge the evidence that treatment in multidisciplinary units lead to overall cost savings as well as higher quality of care. - Audit the current national provision of breast cancer care using accredited auditors. - Implement mandatory reimbursement and care models that mean treatment can only be carried out in specialist breast units. - Introduce a breast unit quality certification scheme that is accredited by an accreditation body. - Join European-wide scientific societies and groups that promote the availability and quality of breast units, andtogether commit to providing access to such units for all patients . Highlights: The 2016 deadline for all patients in the European Union to access breast cancer units has been missed in most countries. Breast units staffed with multidisciplinary teams deliver superior care and quality of life to breast cancer patients. Treatment in multidisciplinary units leads to overall cost savings as well as higher quality of care. There is an urgent need to establish specialist and certified breast units in all countries.